Daisy for president - Peschke, M. (Marci); Pilz, MH (Edina, Minn. : Magic Wagon, 2011)
Min, DeShaye, and Blanca nominate Daisy for student council president, but Daisy is not sure she wants to go up against bossy Madison, who has all but declared herself the winner.
5.6
3-6
3-6
Keywords: Elections -- Juvenile fiction; Mexican Americans -- Juvenile fiction; Schools -- Juvenile fiction; Elections -- Fiction; Mexican Americans -- Fiction; Schools -- Fiction; Elections -- Fiction; Mexican Americans -- Fiction; School stories